PENENTUAN FITUR WEBSITE BIDANG PARIWISATA DAN KEBUDAYAAN DENGAN METODE FEATURE-ORIENTED DOMAIN ANALYSIS (FODA) - Muhammad Iqbal; Muhammad Reza Faisal; Irwan Budiman (Lambung Mangkurat University, 2016)
Abstract Determination of the features in creating a tourism and cultures websites is required to find out which features are can be implemented. To help determination of the feature, we can use a domain analysis method Feature-Oriented Domain Analysis (FODA). The method has some step, starting with application review to three sample websites to take on the features. The next step are the context analysis to gain a structure diagram and a context diagram. The next step are the modeling domain which divided into two steps, first, features analysis to get the features of the web application through the features diagram with an explanation through domain terminology dictionary. The next step is the entity-relationship modeling by making entity-relationship diagrams for database creation. The final step are architecture modelings to create a domain architecture for application development that only focus on the features. The results from the feature analysis get 38 mandatory features which be implemented on a web application for tourism and culture.Keywords: Tourism, Culture, Website, Features, Feature-Oriented Domain Analysis Abstrak Penentuan fitur dalam membuat website bidang pariwisata dan kebudayaan dibutuhkan untuk mengetahui fitur yang bisa diimplementasikan. Untuk membantu menentukan fitur tersebut, digunakan analisis domain dengan metode Feature-Oriented Domain Analysis (FODA). Metode tersebut mempunyai tahapan dimulai dari tinjauan aplikasi terhadap ketiga website sebagai sampel untuk mengambil fitur. Selanjutnya tahapan analisis konteks yang mendapatkan diagram struktur dan diagram konteks. Berikutnya tahapan pemodelan domain yang dibagi dua langkah yaitu analisis fitur untuk mendapatkan fitur-fitur pada aplikasi web melalui diagram fitur dengan penjelasan melalui kamus terminologi domain. Langkah berikutnya adalah pemodelan entity-relationship dengan membuat diagram entity-relationship untuk pembuatan database. Terakhir, pemodelan arsitektur dengan membuat arsitektur domain untuk pengembangan aplikasi yang hanya fokus pada fitur. Hasil dari analisis fitur adalah didapatkan sebanyak 38 fitur mandatory yang berarti fitur tersebut wajib diimplementasikan dalam aplikasi web untuk pariwisata dan kebudayaan. Kata kunci: Pariwisata, Kebudayaan, Website, Fitur, Feature-Oriented Domain Analysis